Physical Activity Messages for Youth with Disabilities: An Evaluation of Attitudes, Intentions, and Preferences. Issue 8 (2nd July 2020) - Larocca, Victoria; Arbour-Nicitopoulos, Kelly; Latimer-Cheung, Amy; Bassett-Gunter, Rebecca
ABSTRACT: There is no known research examining the use of strategic messages to motivate youth with physical disabilities (YWPD), or how to create effective messages for them. Guided by the Social Issue Advertising Believability Model (SIABM), the study aimed to: (i) examine the effectiveness of physical activity (PA) messages on YWPD's attitudes and intentions to participate in PA, and (ii) consider factors related to message effectiveness. YWPD (N = 60) were randomized to view one of three PA messages: (a) no youth, (b) non-inclusive, and (c) targeted. Attitudes and intentions to participate in PA were assessed at baseline and immediately following viewing one of the three messages. Participants also evaluated the messages in terms of relevance, believability, attention, and attitudes. Repeated measures ANOVA and median split analyses indicated that attitudes toward PA increased after message viewing for participants with low baseline attitudes, but decreased for participants with high baseline attitudes. No significant changes in intentions emerged. The targeted message was most preferred and evaluated as most believable. Attention paid to the message was the only significant predictor of intention to participate in PA post-viewing (p = .001). PA campaigns should consider being inclusive of YWPD with low attitudes and intentions to engage in PA when developing messages.